Grandes riesgos e información tergiversada e incompleta - Núñez del Prado Simons, Alonso (2017)
The author analyzes the European concept of ‘Large Risk’, a subject which has been misunderstood in Latin America. He defend the Peruvian alternative that prefer the Judicial Review instead of the amount limits; and criticize the Project presented in the Peruvian Congress which pretends the second one, following the Chilean law that has deformed –in his opinion– the original (European) idea.